Legal Protection for Hospitals Against Delay in Payment of Claims by BPJS - Ismawan Adrianto; Sumarno (International Journal of Society and Law, 2024)
Health is a human right and one element of prosperity that must be realized in accordance with the ideals of the Indonesian nation. As intended in the 1945 Constitution of the Republic of Indonesia (UUD 1945) contained in Article 28 H paragraph (1) and Article 34 paragraph (2) and to provide comprehensive social security, the state is developing a National Social Security System for all people Indonesia by establishing Law Number 40 of 2004 concerning the National Social Security System (UU SJSN). As a form of implementation of the SJSN Law, the government issued Law Number 24 of 2011 concerning the Social Security Administering Body (UU BPJS) to accelerate the implementation of the national social security system as a whole, including National Health Insurance (JKN) which will be administered by BPJS Health. This research adopts a normative juridical method, which focuses on analysis of statutory regulations, policy documents, and legal literature relevant to legal protection for hospitals against delays in payment of claims by BPJS. This research discusses Late Fines, Supply Chain Financing (SCF), Dispute Resolution, Termination of Claim Payment Agreements by BPJS. Hospitals have an obligation to provide services to BPJS participating patients and BPJS Health's obligation is to pay hospital claims according to the agreement. The delay in payment of claims by BPJS Health will of course affect the hospital's cash flow. One way to protect hospital interests is to provide legal protection against delays in claim payments by BPJS Health. The first legal protection provided is to use a complaint mechanism. Apart from that, more specific legal protection is also regulated, namely the existence of late fines for BPJS Health which refers to Presidential Regulation Number: 82 of 2018 and cooperation agreements, the SCF program to maintain hospital cash flow, dispute resolution carried out by deliberation and termination of the agreement if it is wrong. one party is proven to have defaulted as stipulated in the cooperation agreement.